Crash course on entrepreneurial learning - Zozimo, Ricardo (Henry Stewart Talks, 2015)
Entrepreneurial learning as a critical means for entrepreneurs to achieve success, The foundations of experiential and observational learning within the context of entrepreneurship, Dynamic understanding of entrepreneurial learning (the social learning cycle)